Practical Noise Model of an Active Electronically Scanning Array - Jian Mi; Kan Wang; Zhao Li; Hongbing Sun (International Journal of Antennas and Propagation)
Active electronically scanning arrays are now widely used in radar and communication systems. The noise characteristics are critical to the system signal-to-noise ratio, thus modeling of the antenna array noise is useful. In this paper, a two-port noise model of an active electronically scanning array is presented, which is more practical than the model in previous publications. In this model, an antenna array with a multistage combiner network is equivalent to a one-stage combiner network, thus the calculation of the noise figure is greatly simplified. Since the model is based on measurable parameters, it can be applied directly to the design of electronically scanning arrays. The noise model of a spaceborne synthetic aperture radar antenna system is displayed for example. Some useful conclusions are got about the noise figure for tapered antenna arrays. For a weighted antenna array with taper efficiency εT, if the gain of low noise amplifiers is sufficiently large, the noise figure of the antenna array is increased by 1/εT, compared to a uniformly weighted array. Besides, the deterioration of the signal-to-noise ratio for a tapered antenna array system originates from the increase of antenna noise temperature, rather than the decrease of antenna aperture gain.